2019
DOI: 10.18203/2349-3291.ijcp20191996
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of congenital heart disease in a tertiary care centre of Northern India

Abstract: Background: Congenital heart disease (CHD) is very common disease and it is the major cause of childhood mortality and morbidity. Not much of Indian data are available particularly from the northern part of the country. It is important to mention that this part of India is unique with respect to its demographic and geographical location. There are needs to further explicate the spectrum and epidemiology of the CHD in this part of the country.Methods: A prospective hospital-based study carried out over a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 10 publications
4
6
1
Order By: Relevance
“…14 We included all form of AVSD in one category. Incidence of AVSD in our study was double that of an Indian study (2.7%), 11 which also did not categorize the type of AVSD. Pakistani study with prevalence of AVSD (10.3%), 10 included only complete type of AVSD.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…14 We included all form of AVSD in one category. Incidence of AVSD in our study was double that of an Indian study (2.7%), 11 which also did not categorize the type of AVSD. Pakistani study with prevalence of AVSD (10.3%), 10 included only complete type of AVSD.…”
Section: Discussioncontrasting
confidence: 90%
“…10 The study done by Mir AB et al, at tertiary care center of north India (study population <14 years of age) showed male 60% and female 40% with male dominance. 11 In contradictory population based Chinese study (0-18 years included), about spectrum of CHD, the girl population (56.3%) dominated the male population (43.8%). 12 Our study is a hospital-based study.…”
Section: Discussionmentioning
confidence: 99%
“…The lower incidence rate of AVSD is attributed that AVSD is usually associated with triosomy 21 and higher attrition rate of children with triosomy may lead to lower incidence of AVSD. 20 In present study the most common cyanotic CHD was tetralogy of Fallot 55.6% followed by DORV in 22.2% cases. This finding is comparable with the similar study done by Patra S et al and compared to low to the similar study done by Abqari S et al 22,18 This low incidence can be explained as authors have included only classical TOF and the other variants of VSD PS physiology are grouped separately.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, this could be the reason for less female child seeking the health-care facilities. 20 In the present study, incidence of cyanotic CHD was 26.5% and acyanotic CHDs was 73.5%. Ventricular septal defect (44%) was the most common CHD found in present study.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation